Posterior reversible encephalopathy syndrome in association with exacerbation of chronic obstructive pulmonary disease: a case report - Khanal, Sushil (BMC Neurol, 2018)
BACKGROUND: Posterior reversible encephalopathy syndrome (PRES) is a reversible clinical and neurological entity. There are varieties of comorbid conditions which are associated with PRES. Chronic obstructive pulmonary disease (COPD) is a rare predisposing factor for the development of PRES. CASE PRESENTATION: A 55 year old female who was being treated for acute exacerbation of COPD developed altered sensorium and multiple episodes of seizure. Characteristic imaging findings and associated clinical symptoms led us to a diagnosis of PRES in our patient. CONCLUSION: Association of PRES and COPD is a rare entity. The diagnosis of PRES should be brought to mind if there is encephalopathy or seizure in COPD exacerbation.